Experimental Study on the Influence of Buried Geothermal Pipes on the Temperature Field of Concrete Roads - Yan Tan; Jun Song; Zhi Chen; Henglin Xiao (Advances in Civil Engineering)
Snow removal is a critical security issue for concrete roads, but geothermal methods can be an environmentally friendly and efficient alternative to traditional approaches for snow removal. In order to obtain fully the change rule of the temperature field of the concrete road under geothermal conditions, observe the relationship between temperature rise and time, and better apply the geothermal buried pipe technology to road snow and ice melting, two concrete road models with the dimension of 1 m × 2 m × 0.45 m are made. The model experiments are carried out under the conditions of 0.8 m/s, 0.85 m/s, and 0.9 m/s of pipeline flow velocity, 15 cm and 25 cm of buried pipe depth, and 10 cm and 15 cm of pipe space. The influence of flow velocity, the buried pipe depth, and space on the internal and surface temperature field of concrete road is studied. The results show that, in the flow velocity test, the temperature of the four-layer measuring points shows an upward trend under different flow velocities. With the increase of initial flow velocity, the temperature rise of the first layer measuring points gradually increases. The temperature rise value of the first layer corresponding to 0.9 m/s is 11.66°C, 4.32°C, and 3.13°C higher than 0.8 m/s and 0.85 m/s, respectively; in the buried depth test, the first layer temperature rise at 15 cm is 1.85°C higher than that at 25 cm; in the space test, when the buried pipe space increases from 10 cm to 15 cm, the temperature rise value of the first layer decreases by 1.2°C. From the above three influencing factors experiments, it can be obtained that the temperature rise stage of the first layer measuring points can be divided into the rapid temperature rise stage within 0–2 hours, the temperature rise one with 2 h–6 h, and stable temperature stage after 6 h. Experimental observation shows that road temperature will be higher than 8°C within 1 h–1.2 h, which can eliminate the road icing temperature conditions to ensure that the road does not freeze. After opening the snow melting system for 6 h, the surface temperature of the road tends to be stable, and there is no significant change. In practical application, open the system 1.5 h in advance so that it can prevent road snow and freezing. After opening the system for 6 h or stopping snowfall and rainfall within 6 h, close the system, and the residual temperature stored in the concrete road is used for deicing and snow melting. Ensuring that the road surface temperature is above 0°C, the heating system is turned on intermittently to save energy. The research provides theoretical support for preventing road snow and freezing.